Unveiling the antibacterial mechanism of resveratrol against Aeromonas hydrophila through proteomics analysis - Fu, Yuying; Zhang, Lishan; Lin, Yi; Zhao, Xinrui; Chen, Haoyu; Zhong, Yicheng; Jiang, Wenjia; Wu, Xiaoyun; Lin, Xiangmin (Frontiers in Cellular and Infection Microbiology, 2024)
This investigation delves into elucidating the mechanism by which resveratrol (Res), a natural polyterpenoid renowned for its antimicrobial properties, exerts its effects on Aeromonas hydrophila, a ubiquitous waterborne pathogen. Our findings underscore the dose-dependent manifestation of resveratrol in exhibiting antibacterial and antibiofilm formation activities against A. hydrophila. Employing a Data-independent acquisition (DIA) based quantitative proteomics methodology, we systematically compared differentially expressed proteins in A. hydrophila subjected to varying concentrations of Res. Subsequent bioinformatics analyses revealed key proteins and pathways pivotal in resveratrol's antimicrobial action, encompassing oxidative stress, energy metabolism, and cell membrane integrity. Validation of the proteomics outcomes was meticulously conducted using the qPCR method at the mRNA level.Dynamic trend analysis unveiled alterations in biological processes, notably the correlation between the cell division-related protein ZapC and resveratrol content.Furthermore, scanning electron microscopy corroborated a significant elongation of A. hydrophila cells, affirming resveratrol's capability to inhibit cell division. In concert, resveratrol emerges as a participant in the cell membrane integrity pathway, biofilm formation, and potentially, the regulation of genes associated with cell division, resulting in morphological elongation. These revelations position resveratrol as a promising natural alternative to conventional antibiotics for treating A. hydrophila infections.